2007
DOI: 10.1007/s11244-006-0129-z
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical catalysts for hydrocarbon combustion

Abstract: International audienceTwo series of electrochemical catalysts were prepared from sputtered Pt thin films onto two kinds of electrolyte membranes, 8 mol% Y2O3-stabilized ZrO2 (YSZ), an O2− conducting oxide and Na3Zr2Si2PO12 (NASICON), a Na+ one; respectively. The thickness of the Pt films varied from 8 to 120 nm. Therefore, the Pt loading was extremely low. The catalytic activity of Pt/YSZ and Pt/NASICON systems has been investigated between 200 and 500 °C for propane and propene, respectively. In spite of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 19 publications
2
23
0
Order By: Relevance
“…Indeed, polarization inducing the migration of O 2-ions from the electrolyte to the Pt surface strengthens the Pt-C 3 H 6 chemical bonds (electron-donor) and weakens the Pt-O bonds (electron-acceptor) [5,11,34]. Considering that at low temperatures, C 3 H 6 is strongly adsorbed on the Pt surface (low oxygen coverage) as already shown in previous studies [11][12][13][21][22][23], positive polarization inhibits oxygen adsorption, thus, as predicted by the Langmuir-Hinshelwood model, decreasing propene conversion.…”
Section: Potentiostatic Transient Nemca Experimentsmentioning
confidence: 71%
See 1 more Smart Citation
“…Indeed, polarization inducing the migration of O 2-ions from the electrolyte to the Pt surface strengthens the Pt-C 3 H 6 chemical bonds (electron-donor) and weakens the Pt-O bonds (electron-acceptor) [5,11,34]. Considering that at low temperatures, C 3 H 6 is strongly adsorbed on the Pt surface (low oxygen coverage) as already shown in previous studies [11][12][13][21][22][23], positive polarization inhibits oxygen adsorption, thus, as predicted by the Langmuir-Hinshelwood model, decreasing propene conversion.…”
Section: Potentiostatic Transient Nemca Experimentsmentioning
confidence: 71%
“…The selected reaction was propene combustion in excess oxygen and the electrochemical catalyst was Pt/ YSZ. Previous studies [13,[21][22][23] have demonstrated that a negative voltage, above 340°C, could promote propene deep oxidation on a Pt/YSZ electrochemical catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…One can assume that this last had a so thin Pd layer that it did not cover the entire surface of the pellet. Billard and Vernoux [24] already reported that low thickness Pt catalysts did not cover all the YSZ support. Therefore, the catalytic activity was very low.…”
Section: Resultsmentioning
confidence: 99%
“…This phenomenon has been applied to improve the behaviour of a wide variety of catalyst in a large number of important catalytic reactions [4]. Recently the NEMCA effect has been successfully applied in environmental catalysis such as in the combustion of hydrocarbons [5][6][7][8][9][10], the oxidation of CO [11,12] and the selective reduction of NO [13][14][15][16][17]. However, apart from previous work of Marwood and Vayenas [18], there have been no further studies of electrochemical promotion on the reduction of nitrous oxide (N 2 O).…”
Section: Introductionmentioning
confidence: 99%